Oxidative status in feline pyometra - Figueiredo, Marta de Sousa (2017)
The oxidative status of the organism is dependent of the balance between oxidant reactants and antioxidant defenses. Oxidative stress develops when the oxidant reactants exceed the antioxidant defenses of the organism. The oxidative stress causes alterations in cellular metabolism and cellular damage. The antioxidant response of the organism can be assessed by determination of individual parameters such as total serum thiols (Thiol) and/or by determination of the total antioxidant capacity (TAC) of the organism. Parameters of oxidative status have proved to be useful biomarkers in several canine and feline diseases. Pyometra is considered one of the most important uterine diseases in cats. However, information about the oxidative status in queens with pyometra is lacking. Therefore, the main objectives of this study were to evaluate the oxidative status of feline pyometra through the determination of serum concentration of Thiol and TAC, and to evaluate the clinical evolution of these antioxidants in the post-ovariohysterectomy period. Serum concentrations of Thiol and TAC (determined by four different methodologies) were assessed in 17 queens with pyometra and in 13 healthy queens submitted to elective ovariohysterectomy (control group). Serum Thiol and TAC were also evaluated in six queens with pyometra at days two and 10 after surgery. Routine histopathology of the reproductive organs was performed in all animals, to confirm pyometra in the diseased queens, and to exclude uterine pathology in the control cats. At presentation, diseased queens presented significantly lower serum concentrations of Thiol and TAC than controls (P<0.001 in both cases). In the queens in which serial determinations of antioxidants were performed, serum Thiol and TAC were significantly higher at day 10 post-surgery than at presentation (P<0.05 in both cases). The results of the present study indicate that pyometra in queens is associated with presence of oxidative stress. Moreover, serum Thiol and TAC tended to evolve to physiologic values after surgery. Therefore, oxidative stress parameters could be useful in assessing the post-operative period in feline pyometra.